Incorporation of Electronic Educational Games and Mental Skills Development in Preschoolers in Public Early Child Care Centres in Rivers State - Okankwu, Elizabeth Amini; A-Okujagu, Helen Sokari (Faculty of Natural and Applied Sciences Journal of Computing and Applications, 2025)
The study examined the relationship between the incorporation of electronic educational games and mental skills development in preschoolers in public early child care centres in Rivers State. The study had two objectives, two research questions, and two corresponding null hypotheses. A correlational research design was adopted, targeting a population of 7,589 preschoolers in nursery three (transition class) in 521 public early child care centres in Rivers State. A sample of 755 preschoolers was selected using a stratified random sampling method. Data were collected using two researcher-designed instruments: The Brain Games Observational Checklist (BGOC) and the Mental Skills Checklist (MSC). The instruments were validated by three experts in Early Childhood/Primary Education, yielding reliability coefficients of 0.83 and 0.78, respectively, established using the split-half method and the Spearman formula. The collected data were analyzed using descriptive statistics (mean and standard deviation) to answer the research questions and inferential statistics (Pearson’s product-moment correlation and multiple regression analysis) to test the null hypotheses at a 0.05 significance level. Findings revealed a significant positive relationship between the use of electronic educational games and the enhancement of mental skills, particularly in counting and reasoning. However, memory games exhibited a weaker relationship with counting due to potential distractions. Based on the findings, recommendations include the modification of electronic educational games to incorporate local content and ensuring that supervisors examine all game materials for age-appropriateness before implementation in early child care centres.